2022
DOI: 10.2337/dc21-1584
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Evidence of Efficacy and Safety of SGLT2 Inhibitors as Adjunctive Therapy in Adults With Type 1 Diabetes: A European Two-Center Experience

Abstract: OBJECTIVE To evaluate real-world efficacy and safety of sodium–glucose cotransporter 2 inhibitor (SGLT2i) use in combination with insulin in people with type 1 diabetes. RESEARCH DESIGN AND METHODS We conducted a retrospective cohort European two-center study. Data on demographics, HbA1c, weight, insulin use, renal function, and adverse events were collected for 199 adults with type 1 diabetes who initiated a SGLT2i adjunct t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 34 publications
2
33
1
Order By: Relevance
“…This treatment is, in type 2 diabetes, safe and simple, thus allowing for it to be prescribed in different clinical settings. However, despite their high efficiency, the risks associated with the use of SGLT-2 inhibitors in individuals with type 1 diabetes should be also borne in mind [ 29 ]. In our study, blood ketones were carefully monitored throughout, with values not reaching the levels of detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment is, in type 2 diabetes, safe and simple, thus allowing for it to be prescribed in different clinical settings. However, despite their high efficiency, the risks associated with the use of SGLT-2 inhibitors in individuals with type 1 diabetes should be also borne in mind [ 29 ]. In our study, blood ketones were carefully monitored throughout, with values not reaching the levels of detection.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, blood ketones were carefully monitored throughout, with values not reaching the levels of detection. Under nonstudy conditions or in regular clinical practice, the risk of diabetic ketoacidosis exists; therefore, the prescription of SGLT-2 inhibitors in individuals with type 1 diabetes is not particularly advised [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the safety profile supported a favorable risk–benefit balance. However, real-world evidence suggested that DKA remains a concern with the use of SGLT2i in autoimmune diabetes [ 38 ]. The recent withdrawal of dapagliflozin as an adjunctive therapy in T1D added to the concerns, although this was a commercial decision and not done for safety reasons [ 39 ].…”
Section: The Clinician’s Perspectivementioning
confidence: 99%
“…A recent comparative retrospective cohort study assessed the use of different SGLT inhibitors and doses on blood glucose of patients with type 1 diabetes and found reduced insulin needs in treated groups. However, glucagon levels were not quantified in the study and therefore, in this setting, the effect on alpha cell function remains unclear ( Palanca et al, 2022 ). Nonetheless, double-blinded studies using inhibitors targeting SGLT1 over SGLT2 will be needed to fully understand the therapeutic potential.…”
Section: Main Textmentioning
confidence: 99%